All the Way to the Top : How One Girls Fight for Americans with Disabilities Changed Everything - Pimentel, Annette Bay (Naperville, Illinois : Sourcebooks Explore, 2020)
Diagnosed with cerebral palsy at birth, Jennifer Keelan grew up battling - and overcoming - the limitations others set for her. From a lack of cutaway curbs and bus lifts to being denied enrollment at her neighborhood school, Jennifer was continually blocked from living the life she wanted. But after discovering the world of disability rights activism, she knew she had to use her voice to change things. When Jennifer was just eight years old, she participated in the Capitol Crawl. The image of Jennifer crawling up the steps of Capitol Hill went viral and helped pressure Congress into passing the Americans with Disabilities Act. A powerfully illustrated biography of Jennifers life and a celebration of youth activism, this book will teach all children that they have the power to make a difference. --
Keywords: Keelan, Jennifer, -- 1981- -- Juvenile literature; Keelan, Jennifer, -- 1981-; United States. -- Juvenile literature; People with disabilities -- Civil rights -- United States; Juvenile literature; Children with cerebral palsy -- Political activity -- United States; Juvenile literature; Discrimination against people with disabilities -- United States; Juvenile literature; People with disabilities -- Legal status, laws, etc. -- United States; Juvenile literature; Picture books; Informational works; Biographies; Juvenile works; Biographies; Picture books; Informational works